Visual assessment tools in tennis - Alderson, J.; Elliott, B. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The ability to analyse high-speed strokes in tennis is at least in-part dependant on a coach's ability to see the critical features of the stroke being analysed. While the eye provides visual feedback of the highest order, there are times when technology can play an important role in assisting a coach to observe specific body movements or alternatively to present pictures of performance to a player. Visual feedback is an integral part of performance feedback. This paper will discuss the different visual approaches that may be used by coaches. A relatively recent development the high-speed opto-reflective motion analysis system, has offered an alternate research design investigating tennis stroke production. Using such a system, results from a service analysis of high performance players will be presented in an endeavour to better understand the interrelationship between the legs and the trunk in the tennis serve.